2016
DOI: 10.3109/13813455.2016.1146773
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 is a negative regulator of hepatic glucose production in the isolated rat liver

Abstract: The mechanism underlying the increased rate of endogenous glucose production from the liver during exercise remains unknown. The cytokine interleukin-6 (IL-6) is known to be released during exercise and is thought that either IL-6 directly or via a "contraction factor" stimulates the release of stored glucose from the liver. Here we show that IL-6 does not directly increase hepatic glucose output (HGO). Moreover, IL-6 infused at the same time as glucagon caused a significant reduction in HGO. IL-6 infused with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
2
4
0
Order By: Relevance
“…SKELETAL MUSCLE IL-6 AND LIVER METABOLISM DURING EXERCISE (12), suggesting that the glucose requirement from the liver during exercise is higher when skeletal muscle IL-6 is lacking due to increased skeletal muscle glucose oxidation. The possibility that knockout of muscle IL-6 increases hepatic glucose output is in accordance with a recent paper showing that infusion of recombinant human IL-6 combined with infusion of glucagon in isolated rat liver decreased glucose output from the liver compared with infusion with glucagon alone, suggesting that IL-6 is a negative regulator of hepatic glucose output when present together with an elevated glucagon concentration (8). Fig.…”
Section: R632supporting
confidence: 88%
See 1 more Smart Citation
“…SKELETAL MUSCLE IL-6 AND LIVER METABOLISM DURING EXERCISE (12), suggesting that the glucose requirement from the liver during exercise is higher when skeletal muscle IL-6 is lacking due to increased skeletal muscle glucose oxidation. The possibility that knockout of muscle IL-6 increases hepatic glucose output is in accordance with a recent paper showing that infusion of recombinant human IL-6 combined with infusion of glucagon in isolated rat liver decreased glucose output from the liver compared with infusion with glucagon alone, suggesting that IL-6 is a negative regulator of hepatic glucose output when present together with an elevated glucagon concentration (8). Fig.…”
Section: R632supporting
confidence: 88%
“…Similarly, hepatic PEPCK mRNA content has previously been shown to increase with a single injection of recombinant IL-6 in rats (3), and hepatic glucose output has been shown to increase with a 4-h infusion of recombinant IL-6 in humans (36). The dissimilarities in the suggested effects of IL-6 on hepatic glucose metabolism in previous studies (3,8,10,36) and the present study may be due to different study designs, species differences, or both.…”
Section: R632supporting
confidence: 50%
“…However, in the experiments underlying this view, subjects exercised at low intensity, while IL-6 was infused to reach a concentration corresponding to high-intensity exercise, and accordingly was unphysiological in the studied condition. Furthermore, other studies have shown that IL-6 deficiency in mice does not impair exercise-induced glucose production [ 37 ], and that IL-6 at physiologically relevant concentrations directly inhibits glucose production from the isolated rat liver exposed to plasma from exercising humans [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…In conclusion, based on an innovative, yet classical cross-circulation procedure, and analysis of muscle extract, the present study has provided evidence that contracting skeletal muscle may produce a hormone with a MW below 2000, which, by directly stimulating hepatic glycogenolysis, causes an increase in the supply of glucose to muscle that varies with the intensity of the contractile activity and, accordingly, with the energy needs. Such a hormone would fill up a gap in the present understanding of the regulation of hepatic glucose production in exercise [ 6 , 12 ]. It would also be in line with the finding that, during sleep, muscle inactivity and reduced metabolic rate and glucose uptake are accompanied by a fall in hepatic glucose output, which cannot be explained by known glucoregulatory mechanisms [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation